2012
DOI: 10.1016/j.devcel.2012.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Arl13b in Primary Cilia Regulates the Migration and Placement of Interneurons in the Developing Cerebral Cortex

Abstract: Coordinated migration and placement of interneurons and projection neurons lead to functional connectivity in the cerebral cortex; defective neuronal migration and the resultant connectivity changes underlie the cognitive defects in a spectrum of neurological disorders. Here we show that primary cilia play a guiding role in the migration and placement of postmitotic interneurons in the developing cerebral cortex, and that this process requires the ciliary protein, Arl13b. Through live imaging of interneuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
256
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(274 citation statements)
references
References 70 publications
9
256
0
4
Order By: Relevance
“…We measured the ability of each construct to rescue normal ARL13B protein expression in the cilia of Arl13b hnn MEFs. Previous work in migrating interneurons has shown that proper localization of ARL13B to the cilium is critical for the rescue of ARL13B null phenotypes; 22 therefore, we did not measure transfected cells that may have grown a cilium but failed to exhibit cilia localization of ARL13B. Instead, only transfected (DsRed-positive) cells possessing an ARL13B-positive cilium were considered to show rescue.…”
Section: Novel Arl13b Variant In Joubert Syndrome S Thomas Et Almentioning
confidence: 99%
“…We measured the ability of each construct to rescue normal ARL13B protein expression in the cilia of Arl13b hnn MEFs. Previous work in migrating interneurons has shown that proper localization of ARL13B to the cilium is critical for the rescue of ARL13B null phenotypes; 22 therefore, we did not measure transfected cells that may have grown a cilium but failed to exhibit cilia localization of ARL13B. Instead, only transfected (DsRed-positive) cells possessing an ARL13B-positive cilium were considered to show rescue.…”
Section: Novel Arl13b Variant In Joubert Syndrome S Thomas Et Almentioning
confidence: 99%
“…On pensait que le centrosome ne pouvait pas s'ancrer à la membrane pour soutenir un cil alors qu'il était engagé dans l'organisation et le remaniement dynamique des microtubules conduisant à la progression des protrusions cellulaires et à la translocation nucléaire. Et pourtant, deux publications ont montré la présence et l'importance du cil primaire des interneurones pendant leur migration tangentielle vers le cortex [41,42,68] Ce petit compartiment isolé pourrait-il concentrer et intégrer des signaux annexes, extrasynaptiques, qui contribuent à la survie, à la plasticité, voire à la fonction des neurones ? Plusieurs maladies neurodégéné-ratives ont été associées à des dysfonctionnements ciliaires.…”
Section: Cils Migrations Neuronales Et Projections Axonalesunclassified
“…Les anomalies de migration qui surviennent pendant le dévelop-pement du cortex cérébral sont responsables de défauts fonctionnels graves, comme l'épilepsie et le déficit intellectuel ; ces signes cliniques sont aussi retrouvés dans les ciliopathies. Le cil primaire que nous avons observé sur les futurs neurones inhibiteurs du cortex cérébral chez l'embryon de souris est un acteur important du dévelop-pement cortical, car il régule la migration et le positionnement ultérieur de ces neurones dans le cortex [1,2].…”
Section: Transformations Accompagnant La Migration Des Neurones Gabaeunclassified
“…Ce défaut ressemble à celui des fibroblastes invalidés pour le cil primaire, qui perdent la capacité de se réorienter vers une zone dépourvue de cellules et de la coloniser [16]. Les neurones GABAergiques mutants pour ARL13b (ADP-ribosylation factor-like 13b), une GTPase adressée à la membrane ciliaire, présentent, en plus des défauts de migration décrits ci-dessus, un fort ralentissement de la migration [2]. Cet effet du cil sur le contrôle de la dynamique de migration n'est pas observé dans les mutants que nous avons étudiés, et n'a pas été décrit dans les fibroblastes.…”
Section: Quelle(s) Fonction(s) Pour Le Cil Primaire Des Neurones Migrunclassified